Antiferromagnetic and spectral properties of two-orbital model of iron-based HTSC. (March 2019) - Neverov, Vyacheslav; Lukyanov, Alexander; Zhumagulov, Yaroslav; Krasavin, Andrey
Abstract: Two-orbital model describing iron-based high-temperature superconductors was studied within the limits of variational cluster approximation. The electron density of states for each orbital, as well as momentum distribution, were calculated; the magnetic ordering was determined. The results obtained are in a good agreement with known experimental data.